2019
DOI: 10.1101/833004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune surveillance in clinical regression of pre-invasive squamous cell lung cancer

Abstract: Before squamous cell lung cancer develops, pre-cancerous lesions can be found in the airways. From longitudinal monitoring, we know that only half of such lesions become cancer, whereas a third spontaneously regress. While recent studies have described the presence of an active immune response in high-grade lesions, the mechanisms underpinning clinical regression of pre-cancerous lesions remain unknown. Here, we show that host immune surveillance is strongly implicated in lesion regression. Using bronchoscopic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Strikingly, clonal HLA LoH was only detected in ES patients in both early-stage and late-stage disease suggesting it is an early event in the evolution of ES tumours. Analysis of HLA LoH in preinvasive lung cancer lesions corroborates this observation where HLA LoH occurred in 34% of squamous carcinoma in situ in ES patients 62 , 8% of adenocarcinoma in situ/minimally invasive adenocarcinoma in ES patients and only 1% of these lesions in NS patients 51 . We propose that the TRM-rich microenvironment of ES lungs where NSCLC grows is a likely driver of this early immune evasion mechanism.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Strikingly, clonal HLA LoH was only detected in ES patients in both early-stage and late-stage disease suggesting it is an early event in the evolution of ES tumours. Analysis of HLA LoH in preinvasive lung cancer lesions corroborates this observation where HLA LoH occurred in 34% of squamous carcinoma in situ in ES patients 62 , 8% of adenocarcinoma in situ/minimally invasive adenocarcinoma in ES patients and only 1% of these lesions in NS patients 51 . We propose that the TRM-rich microenvironment of ES lungs where NSCLC grows is a likely driver of this early immune evasion mechanism.…”
Section: Discussionsupporting
confidence: 70%
“…Pre-invasive LUSC 61 possess mutations in oncogenic drivers including KRAS, EGFR and KEAP1 but a number of these lesions regress to a normal-like state 62 . The presence of CD8 + T cells infiltrating pre-malignant LUSC was proposed to support the elimination of malignant cells 62 . It is tempting to speculate greater TRM-immunosurveillance induced by tobacco smoking may protect from invasive cancers induced by this same insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential role of CIN as biomarker of PMLs progression has been observed in low and high grade PMLs (24,25). These reports showed that high levels of copy number variations was the best predictor of progressive PMLs (24,25) and that immune response is the most likely cause of regression as these lesions contained higher levels of immune infiltration (23,27). These results are supported by transcriptomic analysis of PMLs that indicate immune evasion in the transition to invasiveness (28).…”
Section: Introductionmentioning
confidence: 68%
“…LUSC progresses through a series of premalignant stages characterized by alterations of the normal bronchial epithelium (Figure 1) (20)(21)(22)(23). These endobronchial premalignant lesions (PMLs) are classified as low-grade (squamous metaplasia, mild and moderate dysplasia) and high-grade (severe dysplasia, and carcinomas in-situ) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%